The role of fibrosis, inflammation, and congestion biomarkers for outcome prediction in candidates to cardiac resynchronization therapy: is “response” the right answer? - Beltrami, Matteo; Galluzzo, Alessandro; Brocci, Riccardo Tappa; Paoletti Perini, Alessandro; Pieragnoli, Paolo; Garofalo, Manuel; Halasz, Geza; Milli, Massimo; Barilli, Maria; Palazzuoli, Alberto (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiac resynchronization therapy (CRT) is an established treatment in selected patients suffering from heart failure with reduced ejection fraction (HFrEF). It has been proposed that myocardial fibrosis and inflammation could influence CRT “response” and outcome. Our study investigated the long-term prognostic significance of cardiac biomarkers in HFrEF patients with an indication for CRT. Methods Consecutive patients referred for CRT implantation were retrospectively evaluated. The soluble suppression of tumorigenicity 2 (sST2), galectin-3 (Gal-3), N-terminal portion of the B-type natriuretic peptide (NT-proBNP), and estimated glomerular filtration rate (eGFR) were measured at baseline and after 1 year of follow-up. Multivariate analyses were performed to evaluate their correlation with the primary composite outcome of cardiovascular mortality and heart failure hospitalizations at a mean follow-up of 9 ± 2 years. Results Among the 86 patients enrolled, 44% experienced the primary outcome. In this group, the mean baseline values of NT-proBNP, Gal-3, and sST2 were significantly higher compared with the patients without cardiovascular events. At the multivariate analyses, baseline Gal-3 [cut-off: 16.6 ng/ml, AUC: 0.91, p < 0.001, HR 8.33 (1.88–33.33), p = 0.005] and sST2 [cut-off: 35.6 ng/ml AUC: 0.91, p < 0.001, HR 333 (250–1,000), p = 0.003] significantly correlated with the composite outcome in the prediction models with high likelihood. Among the parameters evaluated at 1-year follow-up, sST2, eGFR, and the variation from baseline to 1-year of Gal-3 levels showed a strong association with the primary outcome [HR 1.15 (1.08–1.22), p < 0.001; HR: 0.84 (0.74–0.91), p = 0.04; HR: 1.26 (1.10–1.43), p ≤ 0.001, respectively]. Conversely, the echocardiographic definition of CRT response did not correlate with any outcome. Conclusion In HFrEF patients with CRT, sST2, Gal-3, and renal function were associated with the combined endpoint of cardiovascular death and HF hospitalizations at long-term follow-up, while the echocardiographic CRT response did not seem to influence the outcome of the patients.